THE EFFECT OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, AND REFERENCE GROUPS ON E-WALLET USAGE DECISIONS IN GENERATION Z MEDIATED BY ATTITUDE - Silvia, Monika Leni; Roosdhani, Mohamad Rifqy (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aimed to look over the effect of Perceived ease of use, perceived usefulness, and reference group on usage decisions mediated by Attitude. This study of the population is quantitative in nature, namely Generation Z, which is all e-wallet users. There were 125 samples used in the study, which were analyzed using the PLS-SEM method with the Smart PLS version 4.0 program. This study found the results that Perceived ease of use and reference group have a positive and significant effect on usage decisions, perceived usefulness on Attitude has a positive and significant impact, Perceived ease of use on usage decisions mediated by Attitude has a noteworthy and favorable impact, and reference group on usage decisions mediated by Attitude has a positive and significant impact.